Is Banning Texturized Implants to Prevent Breast Implant-Associated Anaplastic Large Cell Lymphoma a Rational Decision? A Meta-Analysis and Cost-Effectiveness Study. (25th November 2019) - Danilla, Stefan V; Jara, Rocio P; Miranda, Felipe; Bencina, Francisco; Aguirre, Marcela; Troncoso, Ekaterina; Erazo, Cristian A; Andrades, Patricio R; Sepulveda, Sergio L; Albornoz, Claudia R
Abstract: Background: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is an emergent disease that threatens patients with texturized breast implants. Major concerns about the safety of these implants are leading to global changes to restrict the utilization of this product. The principal alternative is to perform breast augmentation utilizing smooth implants, given the lack of association with BIA-ALCL. The implications and costs of this intervention are unknown. Objectives: The authors of this study determined the cost-effectiveness of smooth implants compared with texturized implants for breast augmentation surgery. Methods: A tree decision model was utilized to analyze the cost-effectiveness. Model input parameters were derived from published sources. The capsular contracture (CC) rate was calculated from a meta-analysis. Effectiveness measures were life years, avoided BIA-ALCL, avoided deaths, and avoided reoperations. A sensitivity analysis was performed to test the robustness of the model. Results: For avoided BIA-ALCL, the incremental cost was $18, 562, 003 for smooth implants over texturized implants. The incremental cost-effectiveness ratio was negative for life years, and avoided death and avoided reoperations were negative. The sensitivity analysis revealed that to avoid 1 case of BIA-ALCL, the utilization of smooth implants would be cost-effective for a risk of developing BIA-ALCL equal to or greater than 1:196, and there is a probability of CC with smooth implants equal to or less than 0.096. Conclusions: The utilization of smooth implants to prevent BIA-ALCL is not cost-effective. Banning texturized implants to prevent BIA-ALCL may involve additional consequences, which should be considered in light of higher CC rates and more reoperations associated with smooth implants than with texturized implants.